Determination the serum oestrogen Concentrationand Alkaline phosphatase activity during pregnancy and parturition in oestrus synchronized goat: 1Qayssar Jawad Kadhim, 1Souhayla O. Hussain and 2Ahmed A.Taha - Kadhim, Qayssar Jawad (The Iraqi Journal of Veterinary Medicine, 2014)
This study was designed to investigate the oestrus activity, oestrogen profile and enzymatic change Alkaline phosphatase (ALP) at different stage of gestation and parturition in shami and Iraqi goat. A total of 30 mature female goat of two different breed (fifteen animals / each) were used, their reproduction was followed from January upto July -2013. The investigation included studying oestrus synchronization and allowing the animal to be mated naturally by proven buck. Blood sample were collected before gestation then every fifteen days until parturition. Results showed 100 % of female express estruse after synchronization and (73% and 67%) in shami and Iraqi goats respectively, become pregnant. Regarding the activity of oestrogen, the concentration increase gradually after day (60) of pregnancy and highest value was detected at parturition.Alkaline phosphatase (ALP) rose significantly (p<0.05) at 2nd and 3rd month of pregnancy. Conclusion of the changes, determination of estrogen level and ALP activity will serve as a base line data for monitoring the change during pregnancy and parturition.